AGE GROUP ANALYSIS OF DIABETIC PATIENTS THROUGH RTD AND CETD FUZZY MATRIX MODELS - N.Mythili; Dr.D.Vijayan; D.Niraja (The Bioscan, 2026)
The primary objective of this study is to identify the most prevailing or frequently age group among patients affected by both Diabetes and Blood Pressure(BP) in the Ranipet District .Utilizing the ( Refined-Time Dependent ) RTD and (Combined-Effective Time Dependent) CETD fuzzy matrix models ,the data were collected from 100 individuals cases at rural hospital across the district .By applying fuzzy Matrix modeling methodologies we systematically analysed the collected data to detect patterns of health deterioration across different age groups